2020
DOI: 10.1097/pai.0000000000000885
|View full text |Cite
|
Sign up to set email alerts
|

Utility and Limitations of Albumin mRNA In Situ Hybridization Detection in the Diagnosis of Hepatobiliary Lesions and Metastatic Carcinoma to the Liver

Abstract: Albumin messenger RNA (mRNA) in situ hybridization is a sensitive and specific biomarker for hepatocellular carcinoma (HCC). Intrahepatic cholangiocarcinoma (ICC) shows variable sensitivity, whereas extrahepatic cholangiocarcinoma (ECC) and metastatic carcinoma are generally negative. We studied the clinical utility and limitations of albumin mRNA detection in a cohort of HCCs, ICCs, ECCs, bile duct adenomas, bile duct hamartomas, and metastatic carcinomas to the liver; and investigated the variability in sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The expression of ALB is generally considered a marker of hepatocytes. Several studies have demonstrated the expression of ALB in iCCA, but the features of these ALB + tumor cells are still unclear 8 , 30 , 31 . Here, we detected a group of ALB-expressing tumor cells at the single-cell level, most of which (79.4%) were present in the S100P-SPP1 + iCCA pps (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of ALB is generally considered a marker of hepatocytes. Several studies have demonstrated the expression of ALB in iCCA, but the features of these ALB + tumor cells are still unclear 8 , 30 , 31 . Here, we detected a group of ALB-expressing tumor cells at the single-cell level, most of which (79.4%) were present in the S100P-SPP1 + iCCA pps (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some potentially promising markers have been introduced, and filamin A was reported to show high positivity (63%) by immunohistochemistry on iCCA ( 43 ). Recently, an in situ hybridization assay for albumin RNA was reported to show 90% sensitivity and 100% specificity for iCCA, particularly for the differentiation of small duct type iCCA and metastatic tumors ( 44 46 ).…”
Section: Pathological Features Of Intrahepatic Cholangiocarcinomamentioning
confidence: 99%
“…Strong and diffuse glutamine synthetase staining and β-catenin nuclear accumulation support the diagnosis of CTNNB1 -mutated HCC (CT-HCC). Albumin mRNA in situ hybridization is a sensitive and specific biomarker for HCC [ 41 ]. Additionally, intrahepatic cholangiocarcinomas (ICCAs) are also frequently positive for albumin mRNA [ 44 ].…”
Section: Immunohistochemical Featuresmentioning
confidence: 99%